Valoracion de tratamientos herbicidas en girasol (Helianthus annuus L.) - Garcia, R.C.=700 1 Labrada, R.
(Es, En)
Ilus., 11 ref.
Keywords: HELIANTHUS ANNUUS; MALEZAS; HERBICIDAS; PARTHENIUM; CUBA; PARTHENIUM HYSTEROPHORUS